A brief discussion of the benefit and mechanism of vitamin D supplementation on coronavirus disease 2019. Issue 1 (January 2021) - Cereda, Emanuele; Bogliolo, Laura; de Stefano, Ludovico; Caccialanza, Riccardo
Abstract : Purpose of review: Vitamin D exerts extraskeletal functions, including immunomodulatory activity, protection against respiratory tract infections and pleiotropic effects on the cardiovascular system. Since the outbreak of the coronavirus disease-2019 (COVID-19) pandemic, several articles have suggested the potential involvement of vitamin D in reducing the risk and severity of the disease. Recent findings: Epidemiological and observational studies support the hypothesis of a protective role of vitamin D but most studies are retrospective or based on small samples. However, the pandemic progression and the increased knowledge on the pathogenesis of COVID-19 have challenged the first evidence, suggesting also potential negative consequences derived by adequate vitamin D status. A cautious interpretation of the significance of low vitamin D25OH levels is advisable. The balance between over-activation of innate immunity and the exhaustibility of the adaptive immune response still needs to be clarified. In addition, the modulation of endothelial function, the down-regulation of renin, angiotensin-converting-enzyme (ACE) and angiotensin genes and the up-regulation of ACE2 expression is still an area of research. Summary: Speculative hypotheses and observational data have suggested a protective role of vitamin D in COVID-19. However, many unanswered questions remain, aberrant detrimental effects of adequate vitamin D25OH levels cannot be excluded and whether its adequacy may prevent the infection or improve clinical outcomes needs to be assessed by adequately sized and designed population-based studies and intervention trials.